BIAS GENDER DALAM UNDANG-UNDANG NO 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA - Khomsinnudin Khomsinnudin; Muhammad Anis Afiqi (TSURAYYA: Journal Education, Economy and Religia, 2026)
The household should ideally be a safe environment for every family member; however, in reality, it often becomes a setting for domestic violence. This study aims to analyze gender bias in Law No. 23 of 2004 concerning the Elimination of Domestic Violence using a library research method with a qualitative approach. Although enacted as an instrument of protection, the law is considered to still contain partialities that may potentially result in legal injustice. The findings indicate the presence of gender bias in five main aspects: the definition of domestic violence, protection obligations, criminal sanctions for perpetrators, victim handling mechanisms, as well as aspects of education and socialization. The law tends to focus primarily on the protection of women, thereby overlooking the protection rights of men or other family members who may also potentially become victims. In addition, the lack of adequate socialization programs hinders the elimination of gender bias in society. Therefore, legal reform that is more inclusive and equitable is necessary so that the legal framework can provide comprehensive protection for all family members without gender discrimination.